THE IMPROVEMENT OF CHILDREN’S INDEPENDENT LIVING SKILLS IN THE CONTEXT OF THE RESTRUCTURING OF CHILDREN’S CARE HOMES - Gudzinskienė, Vida; Raudeliūnaitė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article analyses the improvement of children’s independent living skills in the context of the restructuring of children's care homes. The concept of the restructuring of institutional care is presented. A qualitative-empirical study has been conducted by using the method of a semi-structured interview. The study data were processed by using the method of content analysis. The results of the empirical study are based on the experience of 14 social workers, who work in care institutions, which participate in the restructuring, which consists of the changeover from institutional care to the services that are provided to children, who have become destitute of parental care, in a family and community. Three directions of the improvement of children’s independent living skills in the context of the restructuring of children's care homes have been highlighted: increasing independence in adolescents (the engagement of children in a practical activity and their reasoning by encouraging and stimulating them for an independent activity); the improvement of the organisation of educational process (the increase of practical exercises, the  reduction of the number of nurtures in a household, the increase of an individual communication with a child); the improvement of material basis (fund raising and the redistribution of the resources available).